2003
DOI: 10.1128/jcm.41.11.5333-5336.2003
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Fungal Sinusitis Associated with Trichoderma longibrachiatum

Abstract: We describe allergic fungal sinusitis caused by Trichoderma longibrachiatum in a patient with a history of atopy and asthma. A Gram stain of a sinus biopsy specimen was initially thought to contain yeast cells, but when Trichoderma was recovered in culture, these cells were subsequently recognized as chlamydospores. The patient was successfully managed with a combination of sinus lavage, oral corticosteroids, itraconazole, and allergen immunotherapy. This case also points out that careful scrutiny of direct sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…The clinical experience with azolebased therapies also shows variable outcomes; VRC used mostly in combination with CFG has shown some positive results against deep infections by T. longibrachiatum, T. reesei, and T. viride (7,(21)(22)(23)68). ITC has shown success alone and in combination with AMB and surgical resection against T. longibrachiatum (10,11,25), although according to our susceptibility results the apparent effectiveness of ITC might be only anecdotical. Ketoconazole was successful in a peritonitis case attributed to an unidentified Trichoderma species (15), while there are no reports on the use of PSC against Trichoderma infections.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The clinical experience with azolebased therapies also shows variable outcomes; VRC used mostly in combination with CFG has shown some positive results against deep infections by T. longibrachiatum, T. reesei, and T. viride (7,(21)(22)(23)68). ITC has shown success alone and in combination with AMB and surgical resection against T. longibrachiatum (10,11,25), although according to our susceptibility results the apparent effectiveness of ITC might be only anecdotical. Ketoconazole was successful in a peritonitis case attributed to an unidentified Trichoderma species (15), while there are no reports on the use of PSC against Trichoderma infections.…”
Section: Discussionmentioning
confidence: 79%
“…In the clinical setting, species identification has been based mainly on ribosomal DNA (rDNA) sequences (8,23,28,40), although it has been shown that the use of this locus does not provide sufficient resolution to accurately distinguish closely related species (4,26,41,43). This, together with the poor in vitro activities of commonly used antifungals against Trichoderma isolates, is an impediment for the treatment of Trichoderma infections (11,43) and limits our understanding of the epidemiology of the species.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The genus includes species reported to cause mycoses and allergy in humans (12,31,36,59). Toxin production has also been reported, and some species can be preservative resistant in food products (45,56).…”
Section: Discussionmentioning
confidence: 99%
“…The work of Patric Tang et al, described that primary etiologic agents in Allergic Fungal Sinusits (AFS) are dematiaceous fungi, especially Bipolaris spicifera or Curvularia lunata and in some geographic regions Aspergillus species, and the basidiomycete Schizophyllum commune. Presumably, the disease begins with colonization of the paranasal sinuses by spores of an airborne fungus [7,8]. In our patient inhalation of conidia is thought to be the route of transmission resulting in such rare mycotic infection of maxillary sinuses.…”
Section: Discussionmentioning
confidence: 99%